1996
DOI: 10.1172/jci118493
|View full text |Cite
|
Sign up to set email alerts
|

Histamine and thrombin modulate endothelial focal adhesion through centripetal and centrifugal forces.

Abstract: We examined the contribution of actin-myosin contraction to the modulation of human umbilical vein endothelial cell focal adhesion caused by histamine and thrombin. Focal adhesion was measured as the electrical resistance across a cultured monolayer grown on a microelectrode. Actin-myosin contraction was measured as isometric tension of cultured monolayers grown on a collagen gel. Histamine immediately decreased electrical resistance but returned to basal levels within 3-5 min. Histamine did not increase isome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
185
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(198 citation statements)
references
References 30 publications
(41 reference statements)
10
185
1
2
Order By: Relevance
“…Moreover, it has been demonstrated that intracellular levels of cAMP are tightly coupled to myosin light chain activity (41). Pharmacologic maneuvers that increase intracellular levels of cAMP (42) or cGMP (43) result in a dephosphorylation of myosin, a redistribution of actin and myosin II, and a decrease in endothelial isometric tension, indicating that endothelial permeability is likely coupled to myosin light chain kinase activity. Finally, recent in vivo work has suggested that endotoxin-induced increases in vascular permeability are associated with accumulation of neutrophils and that dysfunction may be coupled to elevations in cGMP (44).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that intracellular levels of cAMP are tightly coupled to myosin light chain activity (41). Pharmacologic maneuvers that increase intracellular levels of cAMP (42) or cGMP (43) result in a dephosphorylation of myosin, a redistribution of actin and myosin II, and a decrease in endothelial isometric tension, indicating that endothelial permeability is likely coupled to myosin light chain kinase activity. Finally, recent in vivo work has suggested that endotoxin-induced increases in vascular permeability are associated with accumulation of neutrophils and that dysfunction may be coupled to elevations in cGMP (44).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, increased actomyosin generated pulling force is important for opening of endothelial cell-cell junctions in response to permeability-inducing factors. 20 By altering the magnitude and direction of the forces that are exerted on cell-cell junctions, actin cytoskeleton rearrangements can change the integrity of VEcadherin-based cell-cell junctions. 21 Thus, a finely balanced regulation of actin network organization, together with myosin-II activity, is needed to produce mechanical forces that drive assembly, maintenance and remodeling of adherens junctions (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…ROCK can phosphorylate the myosin light chain phosphatase targeting subunit (MYPT‐1), leading to inactivation of myosin light chain phosphatase, and accumulation of myosin light chain phosphorylated on Thr‐18 and Ser‐19 by myosin light chain kinase 11, 12. Several reports have suggested that inflammatory mediators promote excess phosphorylated myosin light chain, which may interact with actin to open intercellular junctions, either through contractile or retractile mechanisms 3, 13, 14, 15, 16, 17, 18. Despite these advances, a caveat to using inhibition of RhoA/ROCK to reduce microvascular hyperpermeability is the fact that this pathway is also important for maintaining endothelial barrier function under noninflammatory conditions,17, 19, 20 as RhoA activation near cell borders promotes endothelial barrier integrity 21.…”
Section: Introductionmentioning
confidence: 99%